Validation of Hand Grading Technique of Corpora Lutea in Embryo Recipient Cows - Gamage Dammika Rohan Kumara Perera; Pupulewatte Gedara Anil Pushpakumara; Ponvila Arachchilage Basil Doglas Alexander (Journal of Tropical Life Science)
The success of embryo transfer in cattle may depend on several factors. The blood progesterone level of the embryo recipient would be one of the main factors secondary to the size and quality of the corpus luteum. Per-rectal palpation and by-hand grading of corpora lutea have been practiced routinely, even under commercial embryo transfer programs in cattle. This experiment aimed to evaluate the accuracy of the per-rectal hand grading technique of mid-phase corpora lutea in embryo recipient cows. A group of healthy cows (Friesian× Jersey, n=25), which had been selected as recipient animals with the special consideration of reproductive history in an embryo transfer program, was used in this study. Estrous of those animals were synchronized using a standard progesterone intravaginal devise-PGF2α protocol. Conventional evaluation and grading of corpora lutea were conducted at the per-rectal hand grading as 'A', 'B', 'C' and 'Cystic' (If diameters; < 1cm=C, 1-1.9cm=B, 2-2.5cm= A, >2.5cm= Cystic). In this study, the accuracy of those hand-grading techniques was evaluated using ultra-sound scanning technology on the same day. Identification accuracy of grades C, B, A, and Cysts in hand grading technique was 45%, 56%, 67%, and 50%, respectively. The average accuracy in the hand grading technique was 52%, and identification accuracy as suitable (A or B) corpora lutea for embryo transfer was 76%. Results raised the 24% probable loss of embryo transferrable recipients due to the hand-grading technique. Further, 8% of unsuitable cows can be selected as embryo recipients due to the practice of hand-grading techniques at embryo transfer programs. Although higher accuracy is a characteristic of the hand grading technique, the technology causes considerable loss due to inaccurate selection probability of recipients at embryo transfer programs.